Surgical services for children in developing countries - Bickler S.W; Rode H. (The World Health Organization, 2002)
There is growing evidence that childhood surgical conditions, especially injuries, are common in developing countries and that poor care results in significant numbers of deaths and cases of disability. Unfortunately, however, surgical care is not considered an essential component of most child health programmes. Strategies for improving paediatric surgical care should be evidence-based and cost-effective and should aim to benefit the largest possible number of children. The most likely way of achieving policy change is to demonstrate that childhood surgical conditions are a significant public health problem. For paediatric purposes, special attention should also be given to defining a cost-effective package of surgical services, improving surgical care at the community level, and strengthening surgical education. Surgical care should be an essential component of child health programmes in developing countries.